The Distribution of Pseudodiaptomus marinus in European and Neighbouring Waters—A Rolling Review - Marco Uttieri; Olga Anadoli; Elisa Banchi; Marco Battuello; Şengül Beşiktepe; Ylenia Carotenuto; Sónia Cotrim Marques; Alessandra de Olazabal; Iole Di Capua; Kirsten Engell-Sørensen; Alenka Goruppi; Tamar Guy-Haim; et al. (Journal of Marine Science and Engineering, 2023)
Among non-native copepods, the calanoid Pseudodiaptomus marinus Sato, 1913 is the species probably spreading at the fastest pace in European and neighbouring waters since its first record in the Adriatic Sea in 2007. In this contribution, we provide an update on the distribution of P. marinus in the Mediterranean and Black Seas, along the Atlantic coasts of Europe, in the English Channel and in the southern North Sea. Starting from a previous distribution overview, we include here original and recently (2019–2023) published data to show the novel introduction of this species in different geographical areas, and its secondary spreading in already colonised regions. The picture drawn in this work confirms the strong ability of P. marinus to settle in environments characterised by extremely diverse abiotic conditions, and to take advantage of different vectors of introduction. The data presented allow speculations on realistic future introductions of P. marinus and on the potential extension of its distribution range.